A STUDY ON JOB SATISFACTION AMONG MEDICAL TRANSCRIPTIONISTS - Ravi Chinnathambi and T. G. Vijaya (Abhigyan, 2010)
Medical Transcriptionists represent the work force of the future, including its opportunity and challenges. While the growing market throws a lot of opportunity to increase the manpower, equally growing competition offers tough challenge to retaining the trained and experienced man power. This study aims at analyzing the factors that influence job satisfaction, both positively and negatively across the different levels and demographic characteristics. The study throws light on factors that organizations should focus on to promote employee productivity and reduce levels of turn over in this industry